Effect of filling technique on the bond strength of methacrylate and silorane-based composite restorations - Fernanda Weingartner MACHADO; Fernanda Blos BORGES; Maximiliano Sérgio CENCI; Rafael Ratto de MORAES; Noéli BOSCATO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The bond strength of methacrylate (Z350, 3M ESPE) and silorane (P90, 3M ESPE) restorations, using different cavity filling techniques, was investigated. Cavities (6 × 3 × 3) in bovine teeth were filled using bulk, oblique, or horizontal increments. A push-out test was carried out after 24 h. Data were statistically analyzed (α = 5%). Methacrylate-based composites and the horizontal filling technique showed the highest bond strength values (10.2 ± 3.9, p < 0.05). Silorane-based composites showed no statistically significant differences regarding the filling techniques (p > 0.05).